Efektivitas Pemberian Deksametason dalam Memengaruhi Durasi Perawatan di Rumah Sakit Pada Operasi Bedah Pintas Arteri Koroner Off Pump - Rally Galang Pratama Putra; Dudy Arman Hanafy; Dicky Aligheri Wartono; Pribadi Wiranda Busro; Bagus Herlambang (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: The off pump coronary artery bypass surgery (OPCAB) technique is expected to be able to eliminate the side effects and complications caused by the use of a cardiopulmonary bypass (CPB) machine. However, this technique is not completely free from side effects or complications. One of the effects that can be caused is an increase in the systemic inflammatory response, so that the duration of hospitalization becomes longer. This is aim of this study to conduct a study of the administration of dexamethasone for reduced the length of hospital stay in patients undergoing OPCAB surgery. Methods: This was an analytic observational study with sixty patients who underwent OPCAB surgery and were randomized to either dexamethasone or placebo groups of 30 people each. Clinical results were analyzed. Results: The length of stay in the dexamethasone group compared to the placebo group was consecutive (5 (5-8) days vs 6.5 (5-30) days; p=0.04) so that there was a significant difference. Other clinical outcomes in the dexamethasone group were better than the placebo group, in terms of duration of mechanical ventilation (p=0.03) and intensive care unit stay (p=0.03). There were significant differences in inflammatory markers between the two groups: interleukin-6 (p=0.0001), procalcitonin (p=0.0001), and C-reactive protein (p=0.0001) were lower in the dexamethasone group. Conclusion: Preoperative dexamethasone in patients undergoing off-pump coronary artery bypass is effective in reducing the length of hospital stay and controlling postoperative inflammatory reactions.